Cryptococcal meningitis in an immunocompetent individual: A case report - Suman Acharya (Wiley, 2021)
Abstract Cryptococcal meningitis (CM) is mostly seen in immune‐compromised patients and rarely occurs in immune‐competent individuals. Immunocompetent individuals with CM present with indolent neurological disease and have better clinical outcomes after treatment. However, misdiagnosis is common and these patients may suffer from serious complications with high mortality.